Starch-Based Bioplastic Reinforced by Cellulose Nanocrystal Isolated from Water Hyacinth - Fauziah Rismawati; Feronika Heppy Sriherfyna; Firda Aulya Syamani (Jurnal Bahan Alam Terbarukan, 2023)
This study aims to determine the effect of the addition of cellulose nanocrystals (CNC) with different concentrations (0,2,4,6,8,10%) isolated from water hyacinth on tensile strength, elongation, and biodegradability of corn starch bioplastics. CNC isolation was conducted, including alkalization, bleaching, acid hydrolysis, and sonication. After the isolation process, CNC was characterized based on functional group, crystallinity, and morphology surface. Then, the production of starch bioplastic using solution casting was carried out with the addition of CNC. The results showed chemical treatments affected the functional group, increasing the crystallinity index, and removing the fibril structure in water hyacinth fibers. Likewise, the addition of CNC to starch bioplastic fluctuated the tensile strength and elongation. In the biodegradability test, the physical appearance of the bioplastic completely changed. Then, the optimum mass reduction occurred in the 6% CNC on the 10th day.